Expected and Unexpected Consequences of the Educational Expansion in Europe and the US : theoretical approaches and empirical findings in comparative perspective - Hadjar, Andreas [Verfasser]; Becker, Rolf [Verfasser]; Aisenbrey, Silke [Verfasser]; Baier, Dirk [Verfasser]; Barone, Carlo [Verfasser]; Branig, Christian [Verfasser]; Brynin, Malcolm [Verfasser]; Cooper, Barry [Verfasser]; Coutrot, Laurence [Verfasser]; Domalewski, Jaroslaw [Verfasser]; Duru-Bellat, Marie [Verfasser]; Enders, Jürgen [Verfasser]; et al. (Haupt, 2009)
"A main mechanism behind the change in European and North American societies in the second half of the 20th century is the educational expansion, i.e. the increase in educational opportunities and the higher demand for education. Whereas other abstract social processes like modernization have been widely theorized in social science literature, the educational expansion and its consequences in particular have not been well studied. Therefore the main aim of this compilation is to deal with the question of whether the demands of the educational reforms have been fulfilled and which other consequences the educational expansion has had. This book will focus on consequences of the educational expansion for individuals and their life courses as well as for the social structure and other societal areas such as culture and politics. Aspects that will be analysed in the light of educational expansion include participation in education, educational inequalities, labour market outcomes, educational returns, and gender differences as well as crime, life expectancy, and lifestyles. Countries analysed in the book include West European countries like Germany, France, Italy and Spain, East European countries (Hungary, Poland, and the Czech Republic) as well as the US." (Verlag, BIBB-Doku)
Keywords: T 4.5 Soziologie; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 4.3.6 Human Capital; G 1.3.3.1 Qualifikationsverwertung; G 1.3.2.2 Übergänge; G 2.4.5 Gender Mainstreaming; Bildungssoziologie; Bildungsexpansion; Bildungssystem; Soziale Ungleichheit; Bildungsbeteiligung; Bildungsertrag; Einkommen; Arbeitsmarkt; Berufseinmündung; Geschlechtsspezifische Faktoren; Europa; USA; Internationaler Vergleich